Pengembangan Bak Sampah sebagai Solusi Berkelanjutan Mengurangi Sampah di Dusun Jeruk Desa Rengas Kapuas - Indriansyah, Muhammad Rana; Fauzan, Risky; Hadinata, Wahyu Surya; Satria, Cakrawala Bahana; Sutino, Maidir (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This community service initiative is based on an awareness of the environment in Jeruk Hamlet, Rengas Village, Kapuas. Environmental preservation, especially maintaining cleanliness, is crucial for both the hygiene and health of the surroundings. In Jeruk Hamlet, there is a small canal/river that is still used by the local community for daily activities. They use the river water for gardening and personal hygiene. This makes environmental preservation even more important to ensure a clean and healthy environment. The development of trash bins is proposed as a solution because, in certain public areas within Jeruk Hamlet, there are still no trash bins available, such as in mosques, schools, and Islamic boarding schools. These trash bins are then placed in several strategic locations, where people often gather at certain times. The purpose of installing these bins is to encourage local residents to be more environmentally conscious, particularly to prevent waste disposal into the river. The outcome of this initiative is expected to preserve the surrounding environment and raise community awareness about waste management and environmental preservation. The conclusion of this article is hoped to provide a positive contribution to environmental awareness and its impact.